Assessment of Al Qur’an Reading and Writing Program for Islamic Character Development in Higher Education - Baharuddin Baharuddin; Sri Nurhayati; Boubker Azzaoui; Khalid Ilias Basheer Qolamani (IJECA (International Journal of Education and Curriculum Application), 2024)
This research critically assesses the efficacy of the Al Qur’an Reading and Writing Pogram at Universitas X, with a specific focus on its contribution to Islamic character development in the realm of higher education. The study employs a cross-sectional survey methodology to collate a broad spectrum of perspectives from students, lecturers, and university administrators. Data collection encompasses both quantitative and qualitative approaches: quantitative assessments are executed through a 5-point Likert scale, measuring levels of agreement regarding various facets of the Al Qur’an Reading and Writing Program, while qualitative insights are procured via open-ended questions, facilitating more comprehensive responses. The findings reveal a strong consensus among respondents on the pivotal role of the Al Qur’an Reading and Writing Program. There is a marked emphasis on the necessity for enhancements in program scheduling, content quality, and the expansion of its scope to more inclusively encompass the entire university community. Furthermore, the study identifies critical needs for improved governance, elevation in educator standards, and the streamlining of administrative processes, particularly in relation to certification. These results offer a detailed understanding of the Al Qur’an Reading and Writing Program's impact and underscore the need for strategic improvements. By doing so, the study contributes valuable insights to the discourse on Islamic character development in higher education.